2020
DOI: 10.1158/1078-0432.ccr-19-3728
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair–Deficient Rectal Cancer and Resistance to Neoadjuvant Chemotherapy

Abstract: Bristol-Myers Squibb, Kyn Therapeutics, Aduro, and Boehringer Ingelheim. DLR serves on the advisory board of Novartis AAA and has received research funding from Merck and Ipsen Novartis and consulting fees from Lexicon. AV has received research funding from Lilly, Bristol-Myers Squibb, Verastem, BioMed Valley Discoveries, and Silenseed (AV's immediate family member has received research funding from Illumina and reimbursement of travel expenses from Roche). GMN has received meal reimbursement from Intuitive Su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 46 publications
2
116
2
3
Order By: Relevance
“…However, their study only included 29 locally advanced rectal cancers and had no comparison with pMMR patients. Furthermore, Cercek et al recently reported chemotherapy resistance for dMMR tumors 23 , which was inconsistent with our findings. The main reasons for the distinction might be that a portion of patients had metastatic disease and a majority of patients underwent NCRT after receiving initial NCT in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, their study only included 29 locally advanced rectal cancers and had no comparison with pMMR patients. Furthermore, Cercek et al recently reported chemotherapy resistance for dMMR tumors 23 , which was inconsistent with our findings. The main reasons for the distinction might be that a portion of patients had metastatic disease and a majority of patients underwent NCRT after receiving initial NCT in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…Standard treatment for locally advanced rectal cancer is total neoadjuvant therapy (TNT), in which induction chemotherapy with FOLFOX is followed by chemoradiation (chemoRT) before surgery. While most locally advanced rectal cancers are responsive to chemotherapy, a recent study of patients with dMMR/MSI‐H LARC by our group demonstrated that 29% of patients had local disease progression while receiving FOLFOX 65,66 . In contrast, no patients with pMMR/MSS locally advanced rectal cancer progressed and 89% had tumor downstaging 66 .…”
Section: Neoadjuvant and Adjuvant Therapymentioning
confidence: 70%
“…The dMMR phenotype is also predictive of resistance to oxaliplatin-based chemotherapy in metastatic CRC [ 140 ]. Although, in CRC, the presence of dMMR is associated with a weaker response to neoadjuvant chemotherapy (5-FU/oxaliplatin), these tumors are more sensitive to chemoradiation [ 141 ]. Moreover, in patients with metastatic CRC receiving irinotecan-based chemotherapy as the first-line regimen, a relationship between increased sensitivity to irinotecan and dMMR status has been reported [ 142 ].…”
Section: Dna Repairing (Moc-4)mentioning
confidence: 99%